2014
DOI: 10.1158/2159-8290.cd-14-0501
|View full text |Cite
|
Sign up to set email alerts
|

A Gnotobiotic Mouse Model Demonstrates That Dietary Fiber Protects against Colorectal Tumorigenesis in a Microbiota- and Butyrate-Dependent Manner

Abstract: It is controversial whether dietary fiber protects against colorectal cancer because of conflicting results from human epidemiologic studies. However, these studies and mouse models of colorectal cancer have not controlled the composition of gut microbiota, which ferment fiber into short-chain fatty acids such as butyrate. Butyrate is noteworthy because it has energetic and epigenetic functions in colonocytes and tumorsuppressive properties in colorectal-cancer cell lines. We utilized gnotobiotic mouse models … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
296
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(315 citation statements)
references
References 39 publications
4
296
0
Order By: Relevance
“…Epigenetic modulators, such as HDAC2 overexpression, were associated with colorectal cancer progression, and a selective HDAC2 inhibitor was reported to prevent colorectal cancer tumorigenesis in both AOM/DSS mouse models and Apc Min/þ mice (33). A recent study shows that gut microbiota could ferment dietary fiber into butyrate, a class I and II HDAC inhibitor, to exert chemopreventive effect on colorectal cancer in gnotobiotic mouse models (34), suggesting that HDACs are potential targets for colorectal cancer prevention. In addition, epidemiology study suggests that statins attenuated the risk of colorectal cancer (35).…”
Section: Clin Cancer Res; 22(16) August 15 2016mentioning
confidence: 99%
“…Epigenetic modulators, such as HDAC2 overexpression, were associated with colorectal cancer progression, and a selective HDAC2 inhibitor was reported to prevent colorectal cancer tumorigenesis in both AOM/DSS mouse models and Apc Min/þ mice (33). A recent study shows that gut microbiota could ferment dietary fiber into butyrate, a class I and II HDAC inhibitor, to exert chemopreventive effect on colorectal cancer in gnotobiotic mouse models (34), suggesting that HDACs are potential targets for colorectal cancer prevention. In addition, epidemiology study suggests that statins attenuated the risk of colorectal cancer (35).…”
Section: Clin Cancer Res; 22(16) August 15 2016mentioning
confidence: 99%
“…As these agents may have a profound systemic immune effect, it has been suggested that diarrhea could potentially be inflammatory in nature (8)(9)(10). The role of gut microbiota in immune-related inflammation [e.g., through lipopolysaccharides (LPS) or fermentation of butyrates in colonocytes] provides motivation to investigate the relationship between the microbiota and VEGF-TKI-induced diarrhea (11,12). As a first step, we focus on demonstrating that patients with VEGF-TKI-induced diarrhea have a different microbiota population than patients without diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiota could have a key role in fiber fermentation into bioactive metabolite short-chain fatty acids; thus, their role should not be overlooked. In gnotobiotic mouse models colonized with wild-type or mutant strains of a butyrate-producing bacterium, it was shown that dietary fiber could have a potent tumor-suppressive effect in a microbiota-and butyrate-dependent manner (Donohoe et al 2014).…”
Section: Dietary Fibers Short-chain Fatty Acids and Butyratementioning
confidence: 99%
“…Gnotobiotic mouse models colonized with wild-type or mutant strains of a butyrate-producing bacterium demonstrated that dietary fiber protects against colorectal carcinoma in a microbiota-dependent and butyrate-dependent manner (Donohoe et al 2014). Due to high aerobic glycolysis by malignant tumors (Warburg effect), butyrate is metabolized less in tumors where it accumulates and functions as an HDAC inhibitor, stimulating histone acetylation, inhibiting cell proliferation, and inducing apoptosis in cancer cells (Donohoe et al 2014).…”
Section: Dietary Fibers Short-chain Fatty Acids and Butyratementioning
confidence: 99%
See 1 more Smart Citation